Faster cognitive and functional decline in Dysexecutive versus amnestic Alzheimer's subgroups: a longitudinal analysis of the National Alzheimer's Coordinating Center (NACC) database. - Jesse Mez (Public Library of Science (PLoS), 2013)
Objective To compare the rate of cognitive and functional decline in dysexecutive, typical and amnestic subgroups of Alzheimer's disease. Methods 943 participants from the National Alzheimer's Coordinating Center (NACC) database who had a diagnosis of probable AD were followed for a mean of 2.3 years. A dysexecutive subgroup (n = 165) was defined as having executive performance >1.5 SD worse than memory performance, an amnestic subgroup (n = 157) was defined as having memory performance >1.5 SD worse than executive performance and a typical subgroup (n = 621) was defined as having a difference in executive and memory performance of <1.5 SD. Generalized estimating equations (GEE) were used to model decline on the Folstein Mini Mental Status Exam (MMSE), rise on the Clinical Dementia Rating (CDR) sum of boxes and rise on the total Functional Assessment Questionnaire (FAQ). Results Compared with the amnestic subgroup, the dysexecutive subgroup declined 2.2X faster on the Folstein MMSE (p<.001), rose 42% faster on the CDR sum of boxes (p = .03) and rose 33% faster on the total FAQ (p = .01). Rate of change for the typical subgroup fell between that of the amnestic and dysexecutive subgroups for the MMSE, CDR sum of boxes and total FAQ. Among a subset of participants (n = 129) who underwent autopsy, the dysexecutive, amnestic and typical subgroups did not differ in odds of having an AD pathologic diagnosis, suggesting that variation in non-AD pathologies across subtypes did not lead to the observed differences. Conclusions A dysexecutive subgroup of AD has a unique disease course in addition to cognitive phenotype.